Ontology in Neolithic Britain and Ireland: Beyond Animism - Fowler, Chris (Religions, 2021)
A combination of new animism and new materialism has influenced recent interpretations of the Neolithic archaeology of Britain and Ireland, including decorative and figurative productions often referred to as ‘art’. This article queries the appeal to animism in some of this work and considers four alternative ways to react to the use of the term. First it considers contextualizing animism by discussing Descola’s identification of four kinds of ontologies—animism, totemism, analogism and naturalism—outlining examples of practices and material culture involved in each. After examining the effect of applying these to the Neolithic archaeology of Britain and Ireland, it then considers identifying Neolithic practices which seem at odds with animism without boxing these as indicative of other categories of ontology. After noting the wide range of Indigenous ontologies such models attempt to characterize, the article advocates an emphasis on ontological difference and attends to ontological diversity within the Neolithic.